Prevalence of diabetes mellitus among Unimas students and its contributing risk factors - Shahnur, Begum (Universiti Malaysia Sarawak, (UNIMAS), 2010)
A cross-sectional study was conducted with a goal to estimate the prevalence of diabetes mellitus and its contributing risk factors among UNIMAS students. A total of ISO students participated in this study with a response rate of 88%. The respondents were of 19 to 29 years of age and 92.7% of them were 20-24 years old. About 60.7% of the respondents were male; the rest, 39.3%, were female. The estimated prevalence of diabetes was 2% and the mean value of random blood sugar (RBG) was 5.6 mmollI) The study showed that, 26% students have family history of diabetes, 4.6 % were suffering from high cholesterol and 4% high blood pressure, and 2 students were suffering from heart disease. The prevalence of smoking was 16.67%; 13.33% was male and 56% of total smoker were Malay. The percentage of alcohol consumption was 28.68%, majority were Chinese (16.67). The estimated obesity was 26.7%. About 64 % students were consuming unhealthy diet in terms of intake of insufficient amount of fruits and vegetables and 50.7% of respondents consumed fat as >30% of total energy intake/day. The result showed, 36.6 % students were active in achieving sufficient physical activity and 41.3% were insufficient in physical activity. This study revealed a significant association (p < 0.001) of RBG with gender, family history of diabetes and chronic diseases, alcohol consumption, Body Mass Index (BMI), total energy intake, percent of fat, percent of carbohydrate of total energy and physical activity. There was no significant association (p > .0.05) of RBG with age, ethnicity, height and weight. Though, this study focused on UNIMAS students only, but it gives an insight on the diabetes status of university students of Malaysia. The outcome could be the basis for nation wide study to have macro level data for developing a general model of diabetes mellitus. Students and patients might find this report beneficial for planning a healthy life-style and it could be a guideline to reduce the risk factors of diabetes.